ANTAGONISME Trichoderma sp. TERHADAP Alternaria porri PATOGEN PENYAKIT BERCAK UNGU TANAMAN BAWANG MERAH PADA BEBERAPA MEDIA - Yukiko N.K Susandi; Denny S. Sualang; Meisye H.B. Paruntu (Universitas Sam Ratulangi, 2018)
ABSTRACT Alternaria porri is pathogen causes purple blotch disease of shallot, and one of important constraints to increase agricultural production. Trichoderma spp. is one of the biological agents that known have antagonistic ability against the pathogen. This study aims to determine the antagonist Trichoderma sp. against the pathogen of Alternaria porri causes purple blotch disease of shallot on several media. Antagonism test implemented by using dual culture method on PDA media, leaf shallot extract media, and leaf shallot extract media + ½ PDA. The result is Trichoderma sp. is able to inhibit the growth of Alternaria porri on the treatment medium. Based on the inhibit percentage of Trichoderma sp. against A. porri, Trichoderma sp. on PDA media more faster to inhibit than leaf shallot extract media, and leaf shallot extract media + ½ PDA because the good nutritions in PDA media. Keywords: Alternaria porri, Trichoderma sp. purple blotch disease